Novel Trial Design: CHIEF-HF. (March 2021) - Spertus, John A.; Birmingham, Mary C.; Butler, Javed; Lingvay, Ildiko; Lanfear, David E.; Abbate, Antonio; Kosiborod, Mikhail N.; Fawcett, Christina; Burton, Paul; Damaraju, C.V.; Januzzi, James L.; Whang, John
Abstract : Background: The expense of clinical trials mandates new strategies to efficiently generate evidence and test novel therapies. In this context, we designed a decentralized, patient-centered randomized clinical trial leveraging mobile technologies, rather than in-person site visits, to test the efficacy of 12 weeks of canagliflozin for the treatment of heart failure, regardless of ejection fraction or diabetes status, on the reduction of heart failure symptoms. Methods: One thousand nine hundred patients will be enrolled with a medical record-confirmed diagnosis of heart failure, stratified by reduced (⩽40%) or preserved (>40%) ejection fraction and randomized 1:1 to 100 mg daily of canagliflozin or matching placebo. The primary outcome will be the 12-week change in the total symptom score of the Kansas City Cardiomyopathy Questionnaire. Secondary outcomes will be daily step count and other scales of the Kansas City Cardiomyopathy Questionnaire. Results: The trial is currently enrolling, even in the era of the coronavirus disease 2019 (COVID-19) pandemic. Conclusions: CHIEF-HF (Canagliflozin: Impact on Health Status, Quality of Life and Functional Status in Heart Failure) is deploying a novel model of conducting a decentralized, patient-centered, randomized clinical trial for a new indication for canagliflozin to improve the symptoms of patients with heart failure. It can model a new method for more cost-effectively testing the efficacy of treatments using mobile technologies with patient-reported outcomes as the primary clinical end point of the trial. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04252287. Abstract : Supplemental Digital Content is available in the text.